Research Progress of TXNIP as a Tumor Suppressor Gene Participating in the Metabolic Reprogramming and Oxidative Stress of Cancer Cells in Various Cancers - Chen, Yiting; Ning, Jieling; Cao, Wenjie; Wang, Shuanglian; Du, Tao; Jiang, Jiahui; Feng, Xueping; Zhang, Bin (Frontiers in Oncology, 2020)
TXNIP, also known as thioredoxin interacting protein, is a kind of thioredoxin (TRX) binding protein, which can mediate oxidative stress, inhibit cell proliferation and induce apoptosis by inhibiting the function of thioredoxin system. In recent years, TXNIP has attracted attention because of its wide range of functions in cardiovascular diseases, neurodegenerative diseases, cancer, diabetes and other diseases. Accumulating evidence has demonstrated that TXNIP is abnormally expressed in a variety of malignant tumors, and functions as a tumor suppressor in malignancies such as hepatoma, breast cancer, pancreatic ductal adenocarcinoma and lung cancer. We can know that TXNIP can inhibit the proliferation of breast cancer cells by affecting metabolic reprogramming, and can affect the invasion and metastasis of breast cancer through the TXNIP-HIF1α-TWIST signal axis, and TXNIP can also negatively regulate bladder carcinogenesis via inhibiting the activation of ERK induced by stromal cell-derived factor-1/C-X-C chemokine receptor type 4 signal, which can inhibit the proliferation and apoptosis of bladder cancer cells. In this review, we summarized that TXNIP can be regulated by binding to transcription factors or binding proteins, and can also be down-regulated by epigenetic changes or miRNA, and we also summarise the emerging insights on TXNIP expression and functional role in different kinds of cancers, and clarify that it can participate in the metabolic reprogramming and oxidative stress of cancer cells as a tumor suppressor gene to inhibit the proliferation, invasion and metastasis and promote apoptosis of different tumor cells, which has important basic and clinical significance for finding new molecular targets and treatment methods for the diagnosis and treatment of malignant tumors.